The New Wheat Vernalization Response Allele Vrn-D1s is Caused by DNA Transposon Insertion in the First Intron - Muterko, Alexandr; Balashova, Irina; Cockram, James; Kalendar, Ruslan; Sivolap, Yuri (NRC Research Press, 2015)
Vernalization requirement in hexaploid wheat is largely controlled by a series of homoeologous VERNALIZATION (Vrn) genes, Vrn-A1, Vrn-B1, and Vrn-D1. The sequence of the promoter area and first intron of Vrn-D1 were analysed in 77 hexaploid accessions, representing five wheat species (Triticum compactum, Triticum sphaerococcum, Triticum spelta, Triticum vavilovii, and Triticum macha) sampled from different ecogeographic areas within 35 countries. Polymorphism was detected in the Vrn-D1 promoter, resulting in a new Vrn-D1 haplotype (named here, Hap-8T). Analysis of Vrn-D1 intron-1 sequences revealed a novel insertional mutation in a subset of T. spelta and T. compactum accessions. This mutant allele was designated Vrn-D1s. Analysis of the 844 bp insertion revealed it to be a novel transposable DNA element (named DTA_Chimera_KF800714) not previously described in Triticum, belonging to the hAT superfamily. Finally, we describe a PCR-based assay that discriminates the wild-type vrn-D1 allele from the Vrn-D1s allele. Collectively, the work described here highlights the potential of utilizing minor hexaploid wheat species for the identification of novel alleles of agronomic importance.
Keywords: vernalization; Vrn-D1; hexaploid wheat; genetic variation; hATtransposon; flowering time